A Two-Phase VIKOR Model for Track Layout Evaluation of Passenger Rail Stations - Belošević, Ivan; Jovanović, Predrag; Pavlović, Norbert; Milinković, Sanjin (Promet - Traffic&Transportation, 2022)
Passenger stations are transit hubs where several railway lines interchange. They have important roles in providing train operations and passenger services. Interrelations between track layouts and technological performances are important for reducing bottleneck effects and raising the operational effectiveness of rail networks. To the best of our knowledge, in previous research the assessment of track layouts has not been considered with respect to various technological aspects including railway operations, safety, and passenger services but rather as a single criterion for analysis of different individual performance indicators. We propose a new two-phase decision making approach for the complex evaluation of track layout alternatives. The first phase model is a VIKOR method for ranking track layouts by criteria related to: railway capacity, safety issue, and passenger-pedestrian fluctuations. Next, in the second phase, we use marginal analysis to find Pareto front and compare the alternatives ratings by calculating performance-benefit coefficients. To show the applicability of the proposed model, we employ an illustrative example of a passenger rail station and evaluate six different track layout alternatives. The effectiveness of the proposed model is demonstrated comparing the proposed two-phase model with traditional VIKOR.